Sosialisasi Strategi Pengembangan serta Pengenalan Potensi Sumber Daya Manusia pada Anak di Panti Asuhan Al-Hidayah Padang - Meswantri .; Yulasmi .; Yusvi Diana (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
Education is a primary capital that plays a crucial role in improving the quality of human life, particularly for the younger generation as the successors of the nation. Through adequate education, individuals can acquire broad insights and knowledge, enabling them to develop their potential optimally. Quality education serves as a foundation for creating superior human resources (HR) with strong character and the capacity to contribute to national development. Human resource development needs to be carried out through well-directed strategies by utilizing individuals’ inherent potentials, including intellectual, moral-spiritual, independence, and social potentials. These four potentials constitute fundamental aspects in the holistic formation of children’s character and competencies. Intellectual potential supports cognitive abilities, moral-spiritual potential shapes values and attitudes, while independence and social potentials strengthen adaptability and social interaction skills. In this regard, community service activities were conducted to provide guidance for the administrators of Al-Hidayah Orphanage in Padang City. These activities were implemented systematically to provide conceptual and strategic understanding of holistic human resource potential development in children.